Melatonin Alleviates Low-Temperature Stress via ABI5-Mediated Signals During Seed Germination in Rice (Oryza sativa L.) - Li, Ruiqing; Jiang, Meng; Song, Yue; Zhang, Huali (Frontiers in Plant Science, 2021)
With the increasing areas of direct sowing, low temperature (LT) stress drastically threatens rice production all over the world. Exogenous applications of melatonin (MT) serve as one of the effective ways to improve seed germination under various stresses. Here, we found that the melatonin treatment greatly improved the LT-stress induced loss of germination percentages and the weak performance of seedlings under low temperature of constant 20℃ (LT20). This was largely dependent on the activated antioxidant system and enhanced activities of storage substances utilization-associated enzymes. Moreover, we also detected that exogenous feeding of MT significantly increased the biosynthesis of gibberellin (GA) and endogenous MT, but simultaneously inhibited the accumulation of abscisic acid (ABA) and H2O2 under LT20 stress. These results suggested that MT had antagonistic effects on ABA and H2O2. Besides, MT treatment also significantly enhanced the expression of CATALYSE 2 (OsCAT2), which was directly regulated by ABA INSENSITIVE 5 (OsABI5), a core module of ABA-stressed signals, and thus promoted the H2O2 scavenging to reach ROS homeostasis, which consequently increased GA biosynthesis. However, in abi5 mutants, OsCAT2 failed response to LT20 stress, irrespective of MT treatment, indicating that OsABI5 was essential for the MT-mediated seed germination during LT20 stress. Collectively, we here demonstrated that melatonin synergistically interacted with the ABI5-mediated signal to mediate seed germination, partially through the direct regulation of OsCAT2.